The Cultural and Societal Factors Contributing to Domestic Violence in Asia - De SILVA, Banuka; DHARMASIRI , K.S.; DISSANAYAKE , D.M.P.V. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Domestic violence is a significant issue in a number of Asian nations, with deep cultural and societal roots. This literature-based research article focuses on the intersection of cultural and societal factors that contribute to domestic violence in Asia. The paper identifies significant cultural factors, including patriarchal values and beliefs, traditional practises, and religious beliefs, that support and reinforce domestic violence in Asian societies. In addition, the report examines the societal factors, such as poverty, lack of education, and inadequate laws and policies, that contribute to domestic violence in these nations. Additionally, the paper examines the effects of globalisation and modernization on domestic violence in Asia. The paper concludes with a summary of the major cultural and societal factors that contribute to domestic violence in Asia, as well as their intersectional effects. The implications of these factors for addressing and preventing domestic violence in Asian nations are also discussed. The paper concludes with suggestions for future research and interventions aimed at addressing cultural and societal factors that contribute to domestic violence in Asia.